Anifrolumab in lupus nephritis: results from second-year extension of a randomised phase II trial - Richard Furie; Raj Tummala; Brad Rovin; Frederic Houssiau; David Jayne; Eduardo Mysler; Teodora Trasieva; Catharina Lindholm; Jacob Knagenhjelm; Erik Schwetje; Weifeng Tang (Lupus Science and Medicine, 2023)
Objective To characterise the safety and efficacy of anifrolumab in active lupus nephritis (LN) through year 2 of the phase II randomised, double-blind Treatment of Uncontrolled Lupus via the Interferon Pathway (TULIP)-LN trial (NCT02547922) of 2 anifrolumab dosing regimens versus placebo.Methods Patients received intravenous anifrolumab 900 mg for the first 3 doses followed by 300 mg anifrolumab (intensified regimen (IR)), 300 mg anifrolumab (basic regimen (BR)) or placebo every 4 weeks throughout. To continue into Year 2, patients must have achieved at least partial renal response and a glucocorticoid tapering target.Results Of 147 randomised patients, 101 completed Year 1 study treatment; of these, 75 (74%) continued into Year 2 (anifrolumab IR: n=29, BR: n=23 and placebo: n=23). During Year 2, 72% of patients reported ≥1 adverse event (AE); serious AEs were reported in 6.9%, 8.7% and 8.7% of patients (anifrolumab IR, BR and placebo, respectively); 3 patients discontinued treatment due to an AE (anifrolumab IR: n=2 and placebo: n=1) and herpes zoster was reported in 2 patients (anifrolumab IR: n=1 and BR: n=1). The study was ongoing at the start of the pandemic, but no COVID-19 cases were reported. Of the 145 patients receiving treatment, more patients on the IR attained complete renal response at Week 104 compared with those on BR or placebo (27.3% vs 18.6% and 17.8%) and simultaneously achieved sustained glucocorticoid tapering (IR: 25.0%; BR: 18.6% and placebo: 17.8%). The improvements in estimated glomerular filtration rate were numerically larger in both anifrolumab groups versus placebo.Conclusions The safety and tolerability profile through Year 2 of TULIP-LN was generally consistent with Year 1, with promising efficacy results for the anifrolumab IR regimen. Collectively, the results support further investigation of an anifrolumab intensified dosing regimen in larger populations of patients with active proliferative LN.Trial registration number NCT02547922.